2021
DOI: 10.1136/archdischild-2021-321940
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of neonatal herpes simplex virus infections in Germany: results of a 2-year prospective nationwide surveillance study

Abstract: ObjectiveTo assess incidence and burden of neonatal herpes simplex virus (HSV) infections and to explore possible transmission routes.MethodsA 2-year prospective nationwide surveillance study performed in 2017 and 2018. All German paediatric departments (n=464 in 2017, n=441 in 2018) were contacted on a monthly basis to report potential cases of neonatal HSV infections. Infants with a postnatal age of ≤60 days and a positive HSV PCR or HSV culture from skin, mucous membrane, vesicles or conjunctival smear, blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…Tens of studies have documented occurrence of neonatal herpes for over 4 decades in Europe in countries such as Denmark, 45 France, 43 Germany, 46 , 47 Ireland, 48 Israel, 49 , 50 , 51 the Netherlands, 52 , 53 , 54 , 55 , 56 , 57 , 58 Poland, 59 , 60 Russia, 61 Spain, 62 Sweden, 63 , 64 , 65 Switzerland, 66 Turkey, 67 and the United Kingdom (UK). 48 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 However, surveillance for this condition remains overall limited with no data being reported for the majority of countries in Europe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tens of studies have documented occurrence of neonatal herpes for over 4 decades in Europe in countries such as Denmark, 45 France, 43 Germany, 46 , 47 Ireland, 48 Israel, 49 , 50 , 51 the Netherlands, 52 , 53 , 54 , 55 , 56 , 57 , 58 Poland, 59 , 60 Russia, 61 Spain, 62 Sweden, 63 , 64 , 65 Switzerland, 66 Turkey, 67 and the United Kingdom (UK). 48 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 However, surveillance for this condition remains overall limited with no data being reported for the majority of countries in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…In Germany, it was reported during 2017–2018 at 2.4 cases per 100,000 live births. 46 In Israel, it was reported during 2001–2007 at 8.4 cases per 100,000 live births. 51 In Poland, it was reported during 2014–2019 at 69.0 cases per 100,000 live births.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Неонатальные инфекции HSV могут проявляться классическими симптомами (герпетические поражения кожи и слизистых оболочек, судороги), но симптомы также могут быть неспецифическими (лихорадка, плохое питье, вялость) или отсутствовать [45]. При отсутствии кожных поражений диагностика неонатальной инфекции, вызванной HSV, затруднена, в этом случае инфекция ограничивается глазами и/или слизистой оболочкой полости рта [42].…”
Section: неонатальная инфекция вирусом простого герпесаunclassified
“…In the USA, neonatal HSV infection incidence reaches up to 70 per 100 000 live births,3–8 and a single-centre study found that HSV infection in hospitalised neonates was as prevalent as serious bacterial infections 9. In contrast, an incidence of up to 20 per 100 000 live births has been reported in European countries, Australia and Canada 10–16. In Denmark, the incidence of neonatal HSV infection was 3 per 100 000 live births in the 1980s and has not been investigated since then 17…”
Section: Introductionmentioning
confidence: 99%